A Doll's House: A Feminist Critique of Gender Dynamics and Marital Power Structures (The International Journal of Educational Sciences and Arts, 2024)
Henrik Ibsen's play "A Doll's House" is a landmark work in the canon of modern drama, renowned for its critical portrayal of the constraints imposed on women in the 19th century. This article examines "A Doll's House" through a feminist lens, exploring the extent to which the play serves as a critique of gender dynamics and the abuse of power by men within the institution of marriage. By analysing the historical and social context of the play, the characterization of Nora and Torvald Helmer, and the symbolism of the dollhouse, this study highlights how Ibsen exposes the oppressive nature of patriarchal society. Key findings indicate that "A Doll's House" not only challenges traditional gender roles but also advocates for women's autonomy and equality. The play's reception and enduring impact on feminist literature and movements underscore its significance as a powerful cry against the subjugation of women. Through this analysis, the article contributes to a deeper understanding of Ibsen's work and its relevance to contemporary discussions on gender and power.
Keywords: Henrik Ibsen; symbolism of A Doll’s House; gender roles; domestic sphere; marital dynamics; women's liberation